High-intensity cannabis use and hospitalization: a prospective cohort study of street-involved youth in Vancouver, Canada - Hudson Reddon; M.-J. Milloy; Evan Wood; Ekaterina Nosova; Thomas Kerr; Kora DeBeck (BMC, 2021)
Abstract Background There is concern that cannabis use negatively affects vulnerable groups such as youth; however, the relationship between cannabis use and health care utilization has not been well characterized in this population. We longitudinally evaluated the association between daily cannabis use and hospitalization among a prospective cohort of street-involved youth. Methods Data were collected from the At-Risk Youth Study (ARYS) in Vancouver, Canada, from September 2005 to May 2015. Participants were interviewed semi-annually and multivariable generalized estimating equation (GEE) logistic regression was used to examine the relationship between daily cannabis use and hospitalization. Results A total of 1216 participants (31.2% female) were included in this analysis, and 373 (30.7%) individuals reported hospitalization at some point during the study period. In a multivariable GEE analysis, daily cannabis use was not significantly associated with hospitalization (Adjusted Odds Ratio [AOR] = 1.17, 95% Confidence interval [CI] = 0.84, 1.65). We did observe a significant interaction between daily cannabis use and sex (AOR = 0.51, 95% CI = 0.34, 0.77), whereby cannabis use was associated with a decreased odds of hospitalization among males (AOR = 0.60, 95% CI = 0.47, 0.78), yet was not significantly associated with hospitalization among females (AOR = 1.19, 95% CI = 0.84, 1.67). Conclusions The finding that daily cannabis use was not associated with hospitalization among street-involved youth is encouraging given the high rates of cannabis use in this population and the expansion of cannabis legalization and regulation. Future studies, however, are warranted to monitor possible changes in the consequences of cannabis use as cannabis legalization and regulation increase internationally.